A study of the drug secukinumab in the treatment of palmoplantar psoriasis. (1st April 2020) - Gottlieb, A.B.; Kubanov, A.; van Doorn, M.; Sullivan, J.; Papp, K.A.; You, R.; Regnault, P.; Frueh, J.A.
Summary: Palmoplantar psoriasis is a chronic (long term) and difficult‐to‐treat form of psoriasis that affects the palms of the hands and the soles of the feet. The disease causes reddish, scaly plaques on the palms and/or soles with or without the presence of such scales elsewhere on the body. Since palms and soles are affected, the patient can have serious issues in carrying out tasks of daily life such as walking, bathing and eating. This can lead to severe disturbance of their quality of life, and such patients may withdraw socially or suffer from depression and lack of confidence. A drug called secukinumab has been shown to offer rapid and long‐lasting effectiveness in treating patients with plaque psoriasis (psoriasis with scales on back, trunk, hands and legs); however, its effect on palmoplantar psoriasis had not been exclusively studied. A randomized control trial is a type of clinical trial in which patients are randomly assigned to a treatment group, and there is also a control group who do not receive any of the treatments being studied. GESTURE, the largest and longest duration randomized controlled study, was conducted to assess the efficacy and safety of secukinumab in people with palmoplantar psoriasis. Both the immediate (16 weeks) and long‐term (2.5 years) results were evaluated. Treatment with secukinumab resulted in quick improvements (starting as early as Week 2) in these patients and the Week 16 results proved the efficacy of secukinumab in palmoplantar psoriasis. The patients were further treated and followed‐up until 2.5 years to understand if the effects are continued or if the disease returns (known as relapse). The 2.5‐year results confirmed that secukinumab treatment resulted in long‐lasting effectiveness in patients with palmoplantar psoriasis. Patients experienced improved hand and feet functioning and therefore improved quality of life. No safety issues were identified. This is a summary of the study: Sustained efficacy of secukinumab in patients with moderate‐to‐severe palmoplantar psoriasis: 2.5‐year results from GESTURE, a randomized, double‐blind, placebo‐controlled trial